Severe periodontitis associated with Marfan syndrome- an existence or a co-existence. - Bindu Madhuri.P5Aravind Kumar P. MDS1, Indeevar Reddy MDS2, Rasagnya.Y3, Divya.V4 (Journal of Biomedical and Pharmaceutical Research, 2016)
Marfan syndrome is the most common dominant autosomal genetic disorder of connective tissue origin. Over the years various diagnostic criteria have been developed for this entity, the earliest among them is the Berlin Nosology, which classifies this condition mainly based on its physical characteristics.Oral manifestations associated with this condition are poorly documented and periodontitis associated with Marfan syndrome is still a controversy. This article report a case of Marfan syndrome with periodontal involvement, the patient was successfully managed with nonsurgical periodontal therapy. Keywords: Connective tissue disorders, Marfan’s syndrome,Dolichocephalia,Fibrillin.